Multimodal mapping: Using mind maps to negotiate emerging professional communication practices and identity in higher education - Grant, T.; Archer, A. (South African Journal of Higher Education, 2019)
Mind or concept maps have long been viewed as helpful tools to plan texts. The pedagogical focus is often focused on the end product as material artefact, with less pedagogical or assessment attention being paid to the process of mind mapping. A process-product approach to text and text-in-use can fulfil a variety of pedagogical goals that allow participants in a professional communication course to collaboratively negotiate meaning-making. By presenting mind maps in class and receiving immediate peer feedback, students have the opportunity to redesign their work to enhance understanding. This article uses a multimodal social semiotic approach as well as the notion of authorial stance (defined multimodally) to analyse a mind map, as both artefact and presentation. The analysis shows how a particular student transforms her work and thinking during in-class engagement. Besides turn-taking and experiential participation as communicator and audience, this negotiation of meaning-making contributes to graduate work-readiness. We argue that these scaffolding and scaffolded activities act to engage student identity formation as emerging professionals for the workplace.